Chemical analysis at Dow Chemical Company laboratory - Dow Chemical Company (1944)
General view of laboratory technicians analyzing assorted materials in a Dow Chemical Company laboratory. Per notations accompanying the photograph, Bill Herrick (left) is analyzing calcium chloride, which was used for the production of Dowflake, while Dick Shilander (center) and Leonard Burns (right) are using an apparatus to determine the specific gravity of Nail Plant liquors.
Keywords: Employees; Industries; Scientific apparatus and instruments; Dow Chemical Company; Glassware; Laboratories